A model for assessing the gender aspect in economic policy - Rakauskienė, Ona Gražina; Krinickienė, Eglė (Business, Management and Economics Engineering, 2015)
The purpose of research is to develop a conceptual model for assessing the impact of the gender aspect on economic policy at macro– and microeconomic levels. The research methodology is based on analysing scientific approaches to the gender aspect in economics and gender–responsive budgeting as well as determining the impact of the gender aspect on GDP, foreign trade, the state budget and the labour market. First, the major findings encompass the main idea of a conceptual model proposing that a socio–economic picture of society can be accepted as completed only when, alongside public and private sectors, includes the care/reproductive sector that is dominated by women and creating added value in the form of educated human resources; second, macroeconomics is not neutral in terms of gender equality. Gender asymmetry is manifested not only at the level of microeconomics (labour market and business) but also at the level of macroeconomics (GDP, the state budget and foreign trade), which has a negative impact on economic growth and state budget revenues. In this regard, economic decisions, according to the principles of gender equality and in order to achieve gender equality in economics, must be made, as the gender aspect has to be also implemented at the macroeconomic level.